LANDSCAPE TOURISM - AN INTERVENTION PROPOSAL TO BEMPOSTA - da Gama, Luís Filipe Tavares Monteiro; Silva Vidal Saraiva, Alexandra Maria Barros Alves Chaves (European Scientific Journal, ESJ, 2015)
The purpose of this article is to show how the development of landscape tourism activities and environmental education in a rural location with a lower population density, in order to use their natural and cultural resources, and its heritage and landscape. The geographical area, located in the Planalto Mirandês, a region in Trásos- Montes, is characterized by being a very rich territory in natural and cultural resources as well as it has a strong touristic potentiality, presenting a diversity of landscapes and native species, privileged by their location, DINP, with also a vast tangible and intangible heritage. This article was elaborated from a wider research that coincided with my master’s thesis, held at Lusíada University of Porto, under the theme “Arquitectura e Paisagem - O Cais de Bemposta”, under the guidance of Professor Alexandra Maria Saraiva, in 2013|2014. This strategy is supported by the organization of various programs and activities of Landscape Tourism and environmental education, such as the design and planning of a landscape observation route, as well as the proposal of building a pier, in order to support the local fishermen and to promote sporting activities, like nature tours that will be focused on the exploration of its natural, cultural and human resources thus seeking to transform and enhance the site. The proposed project has validated the importance of the intervention in the present architectural heritage and landscape, with the objective of keeping its identity, building up a strategic scenario that maintains the intervention plan. It will be created a network of services and platforms, supported by landscape tourism and its relationship with the Douro River as it still presents itself as a strong enhancer of local attraction